Failure Characteristics and Treatment Measures of Tunnels in Expansive Rock Stratum - Yang, Min; Liu, Naifei; Li, Ning; Xu, Chongbang; Li, Guofeng; Cao, Mingming (Frontiers in Earth Science, 2022)
During the operation period, disasters caused by the expansion of tunnel surrounding rock often occurs, but the understanding of this problem is still insufficient. This study investigated the disaster that occurred in the tunnel based on numerical simulation on a case in Dugongling, China. First, the main diseases, including lining cracks, pavement uplift and cable trench overturning and so on, of the tunnel were investigated in the field. According to the geological data, the expansion and softening of the surrounding rock was likely to be the main cause of lining cracking. Then, this paper proposed a formula for calculating the expansion force of expansive rock when the water content changes. Based on the expansion force calculation formula, the most severely damaged section was numerically analyzed, and the results were compared with the on-site monitoring data. According to the simulation results, the deformation of the surrounding rock and the stress of the supporting structure were studied. The research showed that the expansion and softening of the surrounding rock led to an increase in the load acting on the lining structure, which intensified the development of disasters. Finally, four reinforcement schemes were proposed and simulated, and the best reinforcement scheme was evaluated. The results of this study can provide a reference for the design and construction of this project and similar projects.